ANALISIS SENSITIVITAS UNTUK MENENTUKAN UKURAN TUBING PRODUKSI YANG OPTIMUM DI SUMUR MINYAK - Karmila Karmila; Deny Fatryanto E.W.E (PETROGAS: Journal of Energy and Technology, 2021)
Production planning system is important thing in development phase of oil and gas field. The function is to transport of fluid from reservoir to surface facility until sales export point. In production system, one critical phase is determined production tubing that allow to accommodate optimum production rate both when well flow with natural flow or using artificial lift. Nodal analysis is common method that use to plan of production system. This method can give comprehensive view about whole integrated system. In this research, nodal analysis is used to determine optimum tubing size considering pressure profile that occurs in wellbore. Beggs & Brill method is used after comparison between available empiric and analytic model. This based on from model of flow regime in tubing when the well have big oil and gas ratio. The result of This research shown that tubing size determination have variation between wells. Well 1 will be effective using 4.5” tubing size, well 2 will be effective using 2.375” tubing size and well 3 will be effective using 2.375” tubing size. This determination based on performance curve for individual tubing size to production rate and considering changing in pressure curve (gradient transverse)